Corrosion Inhibition of Mild Steel by Capacitabine in Hydrochloric Acid Medium - Guruprasad, A.M.; Sachin, H.P.; Swetha, G.A. (Asian Journal of Chemistry, 2018)
Corrosion inhibition effect of capacitabine (an anticancer agent) on mild steel was carried out in 1 M HCl media by potentiodynamic polarization, weight loss and electrochemical impedance spectroscopy (EIS) techniques at different temperatures. It has been observed that the inhibition efficiency increased with increase in the concentration of inhibitor and decreased with raise in temperature. Polarization studies shows that the inhibitor acts as mixed type and influence both anodic and cathodic reactions. Similar order of inhibition is observed in weight loss, polarization and electrochemical impedance spectroscopic studies. Inhibitor worked by the phenomenon of adsorption and fits well with Langmuir adsorption isotherm. SEM results revealed the protection of mild steel surface in the presence of capacitabine in the aggressive media.